2005
DOI: 10.1002/ejic.200500383
|View full text |Cite
|
Sign up to set email alerts
|

New Polysulfur‐Nitrogen Heterocycles by Thermolysis of 1,3λ4δ2,2,4‐Benzodithiadiazines in the Hydrocarbon and Fluorocarbon Series

Abstract: In contrast to thermolysis of 1,3λ4δ2,2,4‐benzodithiadiazine (1) and its 5,6,7,8‐tetrafluoro derivative 2 in dilute (10–3 M) hydrocarbon solutions, which leads to persistent 1,2,3‐benzodithiazolyls in nearly quantitative yields, the thermolysis of 1 and 2 (the 6‐6 bicyclic system) in concentrated (0.5 M) solutions at 150–170 °C results in complex mixtures of various polysulfur‐nitrogen heterocycles, in particular differently fused 5‐5‐6, 5‐6‐7 and 5‐6‐6‐6 polycyclic systems that were previously unknown. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…For crystal engineering, these compounds are promising due to unlike charges on their S and N atoms, causing intermolecular S/N contacts in the solid state 11 together with extended p-systems capable of p-p interactions in the same state. 12 As a result, multidimensional networks can be formed, which are believed to cause non-trivial chemical and physical properties of this type of compounds. [13][14][15][16][17] At the same time, the coordination chemistry of compounds under discussion is not well-developed, and only a limited number of structurally characterized transition metal complexes, including those of Ag, Cd, Co, Cu, Pd, Ru and trimeric peruoro-ortho-phenylenemercury (anti-crown compound), are known.…”
Section: Introductionmentioning
confidence: 99%
“…For crystal engineering, these compounds are promising due to unlike charges on their S and N atoms, causing intermolecular S/N contacts in the solid state 11 together with extended p-systems capable of p-p interactions in the same state. 12 As a result, multidimensional networks can be formed, which are believed to cause non-trivial chemical and physical properties of this type of compounds. [13][14][15][16][17] At the same time, the coordination chemistry of compounds under discussion is not well-developed, and only a limited number of structurally characterized transition metal complexes, including those of Ag, Cd, Co, Cu, Pd, Ru and trimeric peruoro-ortho-phenylenemercury (anti-crown compound), are known.…”
Section: Introductionmentioning
confidence: 99%
“…97 The authors concluded that the transformation of 12π -electron anti-aromatic dithiadiazines 108 and 109 into aromatic thiadiazoles 1 and 110 is thermodynamically favored. …”
Section: Scheme 51mentioning
confidence: 99%
“…Mayer, Zhivonitko, Marakov and co-workers have reported on the formation of phenothiazines from self-condensation of benzodithiazoyl radicals [50]. Two self-condensation isomer products, each from an intermediate unsubstituted and fluoro-substituted 1,2,3-benzodithiazoyl radical (26d), were synthesised [92]. These crystalline compounds were isolated in very low yield from a reaction mixture (for which the 1,2,3-benzodithiazoyl radical 26b was detected as a minor intermediate), but also in higher (30%) yield by slowly reacting the fluorinated 2-triphenylphosphoranimine-substituted benzodithiazole (26a) at ambient temperature in chloroform (Scheme 27).…”
Section: Synthesis Of Phenothiazinesmentioning
confidence: 99%